If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -45 + z = -47 Solving -45 + z = -47 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '45' to each side of the equation. -45 + 45 + z = -47 + 45 Combine like terms: -45 + 45 = 0 0 + z = -47 + 45 z = -47 + 45 Combine like terms: -47 + 45 = -2 z = -2 Simplifying z = -2
| (-6m^4n^2)(5mn^7)= | | 5+9x=-100 | | 40+x+5x=180 | | -2(3x-5)+8=-6x+18 | | 5+9x=100 | | 65.66*6.28= | | 3y(2x-5y)= | | .9(7x+6)=2.5-(x-3) | | 2c+5-84=3c+6 | | -16x-32=-14x+55 | | 14c+5-32=3c+6 | | 9x-4-7x-10=-8x-11+17x-3 | | Y=.20x+160 | | 14c+35-4=3c+6 | | 0.0m=20.0m+a(12s) | | 25x^2+18=98 | | (5d^2-2g^5)(3g^3-h+4d^2)=0 | | 2p(p)(p)(0+2)+(p+2)=0 | | x-3(-4+9x)=16 | | 8x+3x-9x=4+2 | | 1+-8x=81+2x | | (5d^2-2g^5)-(3g^3-h+4d^2)=0 | | .50x+0.25(30)=42.5 | | [3a+8]=[4a-4] | | sqrt(8n-5)-1=2 | | 64+79= | | 2x+3x+9=6x-16 | | x-12-27x=16 | | 2d-5=d-1 | | 3+8x=4x-1 | | 3+3n=-4+2n | | 0=20+a(12) |